2018
DOI: 10.21276/ambi.2018.05.2.ra06
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Role of the Insect Pollinators in Seed Yield of Cross Pollinated Sesamum indicum from West Bengal, India

Abstract: Among the nine oilseed crops grown in India, Sesamum ranks f ifth for important edible oil crop after groundnut, r a p e s e e d-m u s t a r d , s u n f l o w e r a n d s o y b e a n (www.agricoop.nic.in). India accounts for 39 % area, 27 % production and 40 % export of sesame in the world. India holds a top position in the world in sesame-acreage (24 %) and contribution in export (40 %) (Raikwar & Srivastva, 2013; Iqbal ., 2016; http://www.faostat.fao.o7 rg/site/567/default.aspx#ancor). In India, cultivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…From the present study, it was observed that cropspecific technologies like the installation of bee hives in the mustard field increased the yield of mustard and similar results have also been reported in the studies conducted by Bhowmik et al (2014) and Nagpal et al (2017). Designed crop pollination strategies were found to be preferred and effective strategies with respect to other input-use-based crop productivity enhancement strategies.…”
Section: Mustardsupporting
confidence: 89%
“…From the present study, it was observed that cropspecific technologies like the installation of bee hives in the mustard field increased the yield of mustard and similar results have also been reported in the studies conducted by Bhowmik et al (2014) and Nagpal et al (2017). Designed crop pollination strategies were found to be preferred and effective strategies with respect to other input-use-based crop productivity enhancement strategies.…”
Section: Mustardsupporting
confidence: 89%
“…In addition, mustard oil is utilized in the tanning, hair oil, medication, soap, and vegetable ghee preparation industries. Mustard seeds range in oil content from 37 to 49% (Bhowmik et al, 2014) [1] . Because it contains two essential fatty acids, linoleic and linolenic, and has the least amount of harmful saturated fatty acids of any edible oil, rapeseedmustard oil that is available in India is superior nutritionally to many other edible oils.…”
Section: Introductionmentioning
confidence: 99%
“…Indian mustard, Brassica juncea (L.) Czern & Coss., commonly referred to as sarson or rai (Hindi) is the oldest cultivated dicotyledonous angiosperm plant belonging to Brassicaceae or Cruciferae family which is generally pollinated by insects (Bhowmik, Mitra, & Bhadra, 2014). It is the world's second-largest oilseed crop after groundnut with its distribution in China, Canada, India, Australia, France, Germany, United Kingdom, etc.…”
Section: Introductionmentioning
confidence: 99%